Crossing cultures--stories of the Peace Corps experience - Coverdell, Paul D., 1961- (America in the 21st century (New York, N.Y.), 2010)
Peace Corps volunteers wrote the stories in this book to an audience of classroom students in the United States. The letters are intended to help U.S. students get to know and understand other cultures. Peace Corps volunteers agree to serve in order to meet the three goals of the agency: to provide assistance to the peoples of other countries, to help the people of other countries better understand Americans, and to help Americans better understand other peoples. This book helps fulfill the agency's third goal through remarkable stories by volunteers in the field.